Brentuximab Vedotin in CD30+ Lymphomas - Perini, Guilherme Fleury (Springer Healthcare, 2013)
Monoclonal antibodies (mAb) have become an effective treatment strategy for hematologic malignancies. CD30 is a rational target for therapy due to its limited expression on normal tissues and the strong and uniform expression on malignant cells in classical Hodgkin’s lymphoma (cHL) and anaplastic large-cell lymphoma (ALCL). Brentuximab vedotin, an anti-CD30 antibody-drug conjugate, utilizes the targeting properties of mAb to deliver a cytotoxic agent inside the malignant cell. Brentuximab vedotin has significant clinical activity in patients with relapsed or refractory cHL and relapsed or refractory ALCL, and has the potential to represent a significant advance in modern oncology.